Ergonomic Analysis Using the REBA Method on Worker Posture in the Sorting Section at a Lightweight Brick Company - Iftitah Ruwana; Nanta Sigit (International journal of technology and education research, 2025)
Unergonomic work postures in lightweight brick sorting work are one of the things that can cause the risk of musculoskeletal disorders if not corrected. The purpose of this study is to analyze work postures by applying the REBA method which can evaluate the overall work posture of lightweight brick workers so that recommendations can be obtained to avoid injuries to workers. The data used in the study were images of work postures taken through recordings while workers were performing their work activities. Then, the angles of each part of the neck, back, upper arms, forearms, wrists, wrist rotation, and feet were measured, then the weight of the load, coupling factor and activity score were measured. The results of the study showed that the work postures used by workers when sorting lightweight bricks must be immediately corrected because they show a high level of risk for injury with a REBA score of 10, which means it is included in risk level 4 (dangerous conditions). By reducing dangerous angles on the body parts, a better work posture was obtained with a REBA score of 5, which is included in risk level 3 (medium), thereby reducing the risk of injury to workers.